Development and validation of The Down Syndrome Stigma Scale in a Balinese sample - Suardani, Ni Wayan; Ediati, Annastasia; Winarni, Tri Indah (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Individuals with Down Syndrome are often subjected to social stigma due to their physical appearance. In Indonesia, there was a paucity of research on stigma associated with Down syndrome because the instrument is not available. The study aims to develop and validate the Down Syndrome Stigma Scale in the Indonesian language. Method: An expert panel selected 27 relevant items from the Iranian version of the Stigma Scale towards Down Syndrome. After the translation process, the validity and reliability of the items were evaluated in 79 parents of children with Down syndrome. Results: A factor analysis with factor loading greater than 0.40 was performed. Three factors were identified from 23 items (α=0.928), namely social interaction (10 items; α=0.881), acceptance (8 items; α=0.853), and health-related factors (5 items; α=0.821). Conclusionss The psychometric quality of the Indonesian version of the Down Syndrome Stigma Scale is satisfactory and can be utilized in future research.